Perspective Analysis of Business Competition Supervisory Commission Regarding OJK Circular Letter - fahmi fahmi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
The problem with the lower limit of the tariff lies in determining the amount of the lower limit. Generally, the lower limit is set with the aim of protecting all business actors in the industry without exception, including those who are inefficient and tend to be a burden on the industry in the long term. The lower limit will greatly benefit efficient business actors who should offer the competitive rates they would otherwise receive. The purpose of this study is to explain the Perspective Analysis of the Business Competition Supervisory Commission (KPPU) regarding OJK Circular Letter No. 6/SEOJK.05/2017 Year 2017 in Pekanbaru City, explaining the obstacles faced by the Business Competition Supervisory Commission (KPPU) regarding OJK Circular Letter No. 6/SEOJK.05/2017 Year 2017 in Pekanbaru City This research is a sociological legal research using a positive law enforcement approach. Because there is no study on the results of the OJK Circular Study No. 6 / SEOJK.05 / 2017 and there has been research with the same circular, namely the OJK Circular No. 06 / D.05 / 2013, the recommendation from KPPU to OJK is to revoke the lower limit tariff, because it is considered contrary to the principle of fair business competition. Obstacles faced by the Business Competition Supervisory Commission (KPPU) regarding OJK Circular No. 6/SEOJK.05/2017 in Pekanbaru City